EFFECTS OF GYMNASTICS IN TEACHERS FROM PUBLIC ELEMENTARY SCHOOL, EVALUATED THROUGH PAINFUL SENSITIVITY POINTS (Fiep Bulletin - online, 2013)
This study aimed to verify the benefits acquired in a Gymnastics (GL) in public primary education from 1st to 5th year in the town of Joaquim Tavora (PR), considering the working environment where the teachers are inserted and after evaluating the pain and discomfort through painful sensitivity diagram, it was possible to draw up a programme of gymnastics can compensate the muscles required during the workday of educators. During the journey out of work teachers end up experiencing moments that become responsible for much of the stress of teachers, the main purpose of the GL was to minimize the stress, because stimuli are large, thus breaking the monotony and rigidity, thus improving the quality of life in the school environment. The sample was composed of 9 volunteers, female. The training of gymnastics was held in the morning with duration of 10 minutes during three consecutive months with frequency of 3 weekly sessions. With the results obtained showed a significant improvement in the painful sensitivity points total made by volunteers (p
Keywords: Ergonomics; quality of life; school; teachers